2016
DOI: 10.1186/s12891-016-0943-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography has limited sensitivity for non-tophaceous gout: a comparison study with tophaceous gout

Abstract: BackgroundDual-energy computed tomography (DECT) is a new diagnostic tool for gout, but its sensitivity has not been established. Our goal was to assess the sensitivity of DECT for the detection of monosodium urate (MSU) deposits in non-tophaceous and tophaceous gout, both at the level of the patient and that of the individual joint or lesion.MethodsDECT was performed on 11 patients with crystal-proven non-tophaceous gout and 10 with tophaceous gout and included both the upper and lower extremities in 20/21 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…In a study of 11 patients with crystal-proven non-tophaceous gout and 10 with tophaceous gout, dual-energy CT detected MSU deposits in one or more joint area in seven (64%) patients with non-tophaceous gout but only in three (25%) of 12 joints confirmed by aspiration, whereas MSU deposits were detected in all 10 patients with tophaceous gout. 9 In addition, dual-energy CT can be used to quantify MSU deposition within tophi, with intra-reader and inter-reader intraclass correlation coefficients of 1.0 (for volume measurement) and bias estimates of 0.01 cm 3 ; reliability of dual-energy CT did not vary with different sites or sizes of tophi. 8 False-negative results can be due to less-dense tophi with lower crystal concentrations, small size of tophi / crystals (<2 mm), or technical parameters.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 93%
“…In a study of 11 patients with crystal-proven non-tophaceous gout and 10 with tophaceous gout, dual-energy CT detected MSU deposits in one or more joint area in seven (64%) patients with non-tophaceous gout but only in three (25%) of 12 joints confirmed by aspiration, whereas MSU deposits were detected in all 10 patients with tophaceous gout. 9 In addition, dual-energy CT can be used to quantify MSU deposition within tophi, with intra-reader and inter-reader intraclass correlation coefficients of 1.0 (for volume measurement) and bias estimates of 0.01 cm 3 ; reliability of dual-energy CT did not vary with different sites or sizes of tophi. 8 False-negative results can be due to less-dense tophi with lower crystal concentrations, small size of tophi / crystals (<2 mm), or technical parameters.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 93%
“…37 Baer et al also showed that MSU deposits are more frequently seen in tophaceous gout (sensitivity 100%) than in non-tophaceous gout (sensitivity 64%). 38 Melzer et al in a case report with histopathologic correlation found that DECT only highlighted dense tophi, corresponding to 15 to 20% volume of urate in the tophus. 39 In their study, less dense tophi, despite considerable size, were missed on the color-coded images using standard DECT thresholds.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 96%
“…DECT has moderate sensitivity in non-tophaceous gout and high sensitivity in tophaceous gout. 51 It was noted, however, that DECT had lower sensitivity when restricted to individual crystal-proven gouty joints in non-tophaceous disease or individual erosive lesions in tophaceous gout.…”
Section: Tip 4: Monosodium Urate Crystal Detection and Quantificationmentioning
confidence: 99%
“…These images and analyses are often straightforward, but detection of MSU deposits relates to their size and density and optimal scanner parameters. 51 In general, we recommended a 50%-50% overlay.…”
Section: Tip 4: Monosodium Urate Crystal Detection and Quantificationmentioning
confidence: 99%